ANALYSIS OF THE GROUNDING SYSTEM AT THE 150 KV SERPONG SUBSTATION BASED ON THE IEEE 80-2013 STANDARD - Dwi Cahyono, Aziz; sumarno, Edy Sumarno (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
The grounding system plays an important role in maintaining the operational safety of substations and protecting equipment and personnel from the risk of overvoltage due to disturbances. This study aims to analyze the effectiveness of the grounding system at the 150 kV Serpong Substation based on the IEEE 80-2013 standard. The methods used include direct field measurements using an Earth Tester, simulations using ETAP software version 19.0, and theoretical calculations using formulas compliant with the standard. Measurement results show that the soil resistance values at six locations range from 0.12 Ω to 0.85 Ω, all of which remain below the maximum limit of 1 Ω as required. This demonstrates that the grid rod grounding system configuration is highly effective in reducing soil resistance values and provides consistent and reliable results across all calculation approaches used. Keywords: Grounding, Substation, IEEE 80-2013, Grid Rod, ETAP.